Age at first intercourse, number of partners and sexually transmitted infection prevalence among Danish, Norwegian and Swedish women: estimates and trends from nationally representative cross‐sectional surveys of more than 100 000 women. (19th October 2019) - Hansen, Bo T.; Kjær, Susanne K.; Arnheim‐Dahlström, Lisen; Liaw, Kai‐Li; Juul, Kirsten E.; Thomsen, Louise T.; Frederiksen, Kirsten; Elfström, K. Miriam; Munk, Christian; Nygård, Mari
Abstract: Introduction: Sexual behavior at the population level impacts on public health. Recent representative sexual behavior data are lacking. Material and methods: Cross‐sectional surveys in 2005 and 2012 on women age 18‐45 years randomly selected from the general population in Denmark (n = 40 804), Norway (n = 30 331) and Sweden (n = 32 114). Results: Median (interquartile range) age at first intercourse was 16 (15‐18) years in Denmark, 17 (16‐18) years in Norway, and 17 (15‐18) years in Sweden. Women in the most recent birth cohort had sexual debut at the lowest age, and were most likely to have sexual debut before the legal age of consent. Proportions with debut age ≤14 years among women born 1989‐1994 vs 1971‐1976, odds ratio (95% confidence interval) were: 18.4% vs 10.9%, 1.95 (1.74‐2.18) in Denmark, 12.9% vs 6.3%, 2.38 (2.01‐2.82) in Norway, 17.8% vs 11.4%, 1.75 (1.55‐1.98) in Sweden. Median (interquartile range) number of lifetime sexual partners was 6 (3‐10) in Denmark, 5 (2‐10) in Norway, and 6 (3‐11) in Sweden. The proportion of women reporting >10 sexual partners was also highest in the most recent survey. The percentage with odds ratio (95% confidence interval) in 2012 vs 2005 surveys were: 24.9% vs 22.8%, 1.13 (1.07‐1.18) for Denmark; 23.8% vs 19.8%, 1.27 (1.19‐1.34) for Norway; and 28.3% vs 23.8%, 1.31 (1.24‐1.38) for Sweden. Similarly, the proportion of women reporting ever having had a sexually transmitted infection among women age <30 years were: 29.4% vs 26.4%, 1.21 (1.13‐1.31) in Denmark, 28.9% vs 25.0%, 1.20 (1.10‐1.31) in Norway, and 29.4% vs 22.2%, 1.45 (1.33‐1.58) in Sweden. Conclusions: Scandinavian women reported lower age at first intercourse in younger birth cohorts. Moreover, they reported more lifetime sexual partners and a higher prevalence of ever having a sexually transmitted infection in 2012 than in 2005. Our findings may inform the interpretation of trends in outcomes associated with sexual health, and public health policies.